Pemenuhan Hak Hak Mantan Istri Akibat Putusnya Perkawinan - Nazwa Fajria Poluan; Barzah Latupono; Sabri Fataruba (PATTIMURA Law Study Review, 2023)
ABSTRACT: The fulfillment of the ex-wife's rights must be fulfilled after the breakup of the marriage, in the form of mut'ah maintenance, iddah maintenance, kiswan, maskan. As is commonplace in the relationship between rights and obligations, if the obligation is not carried out it will be detrimental to the party who should get the right. Legal consequences if the ex-husband does not fulfill the rights of the ex-wife, Article 34 paragraph (3) If the husband or wife neglects their respective obligations, they can file a lawsuit with the Court. If a husband who neglects to provide for his wife does not fulfill the decision according to the provisions of Article 196 HIR and Article 207 R.Bg, then the implementation of the decision can be resolved in two ways, namely by force and voluntarily. So that if the husband does not want to carry out the judge's decision to provide maintenance to his wife voluntarily, the judge will carry out the execution. Execution of payment of living expenses for mut'ah, living expenses owed (madhiyah) and living expenses for iddah in the Religious Courts through several stages, namely: Application for execution, paying for execution costs, aanmaning, determination of execution confiscation, determination of execution orders, is carried out in accordance with existing regulations so as not to violate the law as well as making it easier and able to fulfill the rights of the wife after the divorce. This writing begins with conducting research with a type of problem approach research using primary legal materials, tresier legal materials and secondary legal materials. The procedure for collecting legal materials used is library research. The processing and analysis of legal material is carried out using a normative legal research type with a qualitative descriptive method with a description of the problem and analyzing the legal material that has been collected. The result obtained from fulfilling the rights of the ex-wife as a result of the breakup of the marriage is that if it has been decided that the husband must pay for his maintenance to his wife, then he should consciously pay this obligation himself. Rules in Article 41 point (c) of Law Number 1 of 1974 Concerning Marriage. Ex-husbands who do not carry out the obligation to support ex-wives who have been divorced, the Religious Courts have the duty and authority to examine, decide and resolve special civil cases at the first level for people who are Muslim, the implication is that every person who is Muslim can file or sue all special civil cases to the religious court in accordance with the jurisdiction and absolute competence.